Loyalty Building Strategy in East Kalimantan Ecotourism Using Importance Performance Map Analysis - Astrid Napita Sitorus; Ahmad Sirri; Zilfana (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Ecotourism in East Kalimantan holds significant potential as a sustainable tourism model that not only preserves the natural environment but also enhances the welfare of local communities. However, challenges such as low tourist loyalty, limited accessibility, inadequate facilities, and less effective promotion continue to hinder its development. This study aims to formulate strategies for building tourist loyalty in ecotourism by applying Importance Performance Map Analysis (IPMA), which emphasizes variables with high influence but low performance. A mixed-methods approach was employed. Quantitative data were collected from 170 ecotourism visitors and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS), followed by IPMA mapping. Qualitative analysis was conducted through a review of tourism policies and regulations. The variables examined include Place, Findable, Fulfilling, attitude, promotion, interest, and subjective norms. The findings reveal that Place is the most important factor influencing loyalty, but its performance is low, particularly in terms of destination accessibility. Tourist interest plays a crucial moderating role, strengthening the effect of subjective norms and destination quality on loyalty, meaning that higher interest leads to greater likelihood of repeat visits. Subjective norms show relatively weak influence but can be improved through community-based strategies, visitor testimonials, and the use of local influencers. Furthermore, Findable and promotion contribute to strengthening loyalty by expanding digital information reach, while fulfilling and attitude require improvement through consistent tourist experiences and responsive service. Overall, the development of ecotourism in East Kalimantan cannot rely solely on natural attractions but requires a holistic strategy encompassing infrastructure improvement, digital promotion optimization, educational campaigns on ecotourism benefits, and active community involvement. Such an approach is expected to increase tourist satisfaction, foster long-term loyalty, and simultaneously support nature conservation and local cultural sustainability.